Global research on the crosstalk between intestinal microbiome and colorectal cancer: A visualization analysis - Yang, Shanshan; Hao, Shaodong; Ye, Hui; Zhang, Xuezhi (Frontiers in Cellular and Infection Microbiology, 2023)
Background Increasing evidence has shown that the intestinal microbiome (IM) is highly linked to colorectal cancer (CRC). To investigate scientific output, identify highly cited papers, and explore research hotspots and trends in the field of IM/CRC, we conducted a bibliometric and visualized analysis. Methods A bibliographic search regarding IM/CRC research (2012-2021) was implemented on October 17, 2022. The terms attached to IM and CRC were searched for in the titles (TI), abstracts (AB), and author keywords (AK). The main information was extracted from the Web of Science Core Collection (WoSCC). Biblioshiny from R packages and VOSviewer were used for data visualization. Results A total of 1725 papers related to IM/CRC were retrieved. Publications on IM/CRC have grown rapidly from 2012 to 2021. China and the United States were in the leading position for publications in this field and made the most significant contributions to IM/CRC research. Shanghai Jiao Tong University and Harvard University were the most productive institutions. The high-yield authors were Yu Jun and Fang Jing Yuan. The International Journal of Molecular Sciences published the most papers, whereas Gut had the most citations. Historical citation analysis showed the evolution of IM/CRC research. Current status and hotspots were highlighted using keyword cluster analysis. The hot topics include the effect of IM on tumorigenesis, the effect of IM on CRC treatment, the role of IM in CRC screening, the mechanisms of IM involvement in CRC, and IM modulation for CRC management. Some topics, such as chemotherapy, immunotherapy, Fusobacterium nucleatum and short-chain fatty acids could be the focus of IM/CRC research in the coming years. Conclusion This research evaluated the global scientific output of IM/CRC research and its quantitative features, identified some significant papers, and gathered information on the status and trends of IM/CRC research, which may shape future paths for academics and practitioners.